2013
DOI: 10.3892/etm.2013.1460
|View full text |Cite
|
Sign up to set email alerts
|

Lactuside B decreases aquaporin-4 and caspase-3 mRNA expression in the hippocampus and striatum following cerebral ischaemia-reperfusion injury in rats

Abstract: This study aimed to investigate the effects of lactuside B (LB) on aquaporin-4 (AQP4) and caspase-3 mRNA expression in the hippocampus and the striatum following cerebral ischaemia-reperfusion (I/R) injury in rats. Cerebral I/R injury was established in Sprague-Dawley rats by occluding the middle cerebral artery for 2 h and then inducing reperfusion. Rats in the I/R + LB groups were treated with various doses of LB following reperfusion. Neurological deficit scores and brain water content were obtained to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Animals subjected to ischemia-reperfusion also experienced oxidative stress resulting in oxidative imbalance in the striatum. The damage observed in the striatum is consistent with the neuromotor deficits observed in the ischemia-reperfusion group ( 9 ). In this study, neuromotor impairment was demonstrated by the results of the rotarod and open-field tests.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Animals subjected to ischemia-reperfusion also experienced oxidative stress resulting in oxidative imbalance in the striatum. The damage observed in the striatum is consistent with the neuromotor deficits observed in the ischemia-reperfusion group ( 9 ). In this study, neuromotor impairment was demonstrated by the results of the rotarod and open-field tests.…”
Section: Discussionsupporting
confidence: 84%
“…Under conditions of oxidative stress, cells are unable to balance the deleterious effects of ROS through antioxidant mechanisms ( 8 ). Some brain regions, including the striatum, appear to be particularly susceptible to oxidative damage due to ROS levels ( 9 ). The striatum plays an important role in the control of voluntary movements ( 10 ) and contains a high concentration of dopaminergic receptors, which are responsible for motor activation ( 11 ).…”
Section: Introductionmentioning
confidence: 99%